COLLEGE STUDENTS OPINION ON LESBIAN, GAY, BISEXUAL, AND TRANSGENDER/LGBT AND THE ISLAMIC PERSPECTIVE - Indriani Safitri; Salma Allifatu Fuadah (At-Thullab : Jurnal Mahasiswa Studi Islam, 2023)
The purpose of this research is to find out how the opinion of the college students about LGBT and how in the view of Islam. This type of research is qualitative with a descriptive analysis approach. The research subjects were the college students. Data collection techniques used observation, interviews and documentation as well as questionnaires. The data analysis technique uses inductive, namely analysisthat departs from data and leads to general conclusions. The technique for checking the validity of the data used in this study is the cross check technique, namely the technique of crossing out information obtained from sources, so that in the end only the valid ones used to achieve research results. Cross check is done by crossing the information obtained through questionnaires and observation with interviews. The results of the study show that LGBT is very clearly prohibited by Islam. The reasonwhy LGBT is banned is because it violates human nature, meaning that men should marry women, not other men. The reason why LGBT is prohibited is because it is a heinous act, a disgraceful act, violates religious rules, and can cause various sexual diseases. If there is a group that supports LGBT for the sole reason of respecting humanrights, that is wrong and also encourages damage to future generations. What should be done is to make these people (LGBT) aware so they don't violate religious rules. Ofcourse the method is not violence, but is approached slowly and then slowly spoken to.